LANDSCAPES OF CITY AND LANSIA THAT SUFFER (THE CASE OF FATHER'S SPION GLASS, HUANG YONGMEI WORK) - Hin Goan Gunawan (Bambuti, 2019)
Abstract. City is a symbol of modernity. The revival of the Urban Fiction genre in contemporary Chinese literature is driven by writers of the 1970s. It portrays not only urban landscapes with the beauty in their works, but also exposes the souls that suffer in urban spaces. As a symbol of a modern, advanced and civilized life portrayed in Huang Yongmei's short story "Rearview Mirror", it has a dark side. Various changes that move to bring progress do not necessarily change the fate and fortune of urban people who live in it. Instead of being able to enjoy a comfortable and orderly urban space, an elderly former truck driver in the text seems to be moving back in time. Huang Yongmei, literary winner of the 7th Lu Xun literary award (2018), builds allegories about denial of the progress or modernity of today's China. The Rearview Mirror property serves as a kind of reminder of how many parts of past lives have been left behind as we go fast in the flow of change. The magnitude of the progress and the change can only be measured by constantly looking back to its rickety and worn-out past. The suffer of the city people in old age is symbolized with the scene of going backwards, as a healing therapy for the abnormal spine due to sitting behind the wheel for too long. When the city people rush over each day, this old man goes backwards. The complexity of big city problems make the elderly desperate. Widower in old age, deceived by false loyalty, habit of going back to the past have turned into a swimming backstroke. Huang Yongmei has arrived to the point of firmness by keeping the urban’s subject away from the sparkling city life that just makes the little people suffer. The Father's Rearview Mirror text asserts that the urban subject who suffers in his last days leave his hometown, for good.